Planning the South American fluvial territory: inquiries about the deltaic landscape of the Gran Rosario - Galimberti, Cecilia (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
The areas of confluence between land and water have been central spaces for urban development throughhout history. However, these areas are highly vulnerable due to their particular water dynamics, their biodiversity and the high demand to which they are subjected. Since the end of the 20th century, water territories, especially those located in strategic geopolitical areas, wetlands and deltas, are subject to numerous transformations. In this sense, in order to investigate the main processes present in these water landscapes, as well as their challenges and opportunities for the planning, we take as a case study the middle delta of the Paraná river, corresponding to the sector of the Metropolitan Area of Rosario. Through a qualitative methodology, we investigate the processes present in this territorial area and their resulting effects, recognizing three major interrelated themes: socio-territorial impacts of productive processes; habitat of inequality; and tourism and recreation; in order to critically analyse on the challenges of planning in this fluvial landscape. The analysis of existing dynamics, as well as of urban-territorial projects and planning policies, allow us to develop a knowledge platform, reflection and exchange necessary to elaborate new strategies of action attentive to the particularities of these amphibious environments.